AKUNTANSI PERFILMAN : PERAN DALAM INDUSTRI PERFILMAN NUSANTARA - Indra Lukmana Putra; Ditya Wardana; Chrismantya D. S. Nugroho (RISTANSI: Riset Akuntansi, 2023)
This study focuses on identifying films as intangible assets using accounting perceptions Research is carried out as an industrial internship agenda that aims to reduce the Gap/distance between academics and practitioners, namely going directly into the industry to find out the obstacles they face. Film Accounting has an accounting role in the film industry. Film Accounting here aims to build a practical accounting concept in the Indonesian film industry as an industrial culture that continues to grow. This study uses a qualitative research design with a case study approach. Data collection was carried out on a primary and secondary basis with the subject of the Indonesian film industry. The results of this study indicate that the role of accounting is found in every stage of the film and different accounting practices are found in the film industry. One of them records film as an asset owned by a film entity. Several obstacles namely royalties, piracy and settlement can be completed as a film accountant role. The conclusion is that renewal and the active role of accountants in the film industry are needed in order to build and resolve the obstacles to the Indonesian film industry.